Aktifitas Pembelajaran Bahasa Inggris di Pondok Pesantren Nurul Hidayah Bantan dalam Meningkatkan Speaking Performance Santri - Sri Kamaliasari; Amrizal Amrizal (Akademika: Jurnal Keagamaan dan Pendidikan, 2021)
This study is aimed to investigate the English learning activities at Nurul Hidayah boarding school in developing students’ speaking performance with their strengths and weaknesses. This research is descriptive qualitative research with triangulation analysis. Methods for obtaining data were carried out through interviews and documentation. English learning activities at Nurul Hidayah Islamic Boarding School are divided into two; activities in the classroom and outside of the classroom. The classroom activities refer to KMI Gontor. The activities outside of the classroom are Daily Conversations, English Video Screenings, English Speech Exercises, and English Contest and Games. The advantages of the activities are that the boarding school already has a good and effective English learning system and method in training the students' English language skills. The student's awareness and interest in speaking English have grown. The language environment has developed. Meanwhile, its weaknesses are that the number of personnel of the language driving organization is still inadequate compared to the total number of whole students. Most of the teachers do not consistent in using English. Outside of classroom activities programs are so limited. Most of the students are tend to use Arabic than English. Most of the students are still facing some difficulties in memorizing vocabulary and in pronouncing English words. The correction systems toward the language mistakes are still low.